Strategi Pemasaran Jasa Pendidikan dalam Membangun Citra di Sekolah Dasar Islam - Afika Nur Jannah; Nurul Ulfatin; Imam Gunawan; Afika Nur Jannah; Nurul Ulfatin (Universitas Negeri Malang, 2023)
Abstract: This study aims to describe; (1) image of Islamic Elementary School Mohammad Hatta; (2) educational services marketing strategy for image to the community at SD Islam Mohammad Hatta; (3) the success of the results of the marketing strategy for image to the public. This study used a qualitative approach with descriptive case study research. The location of this research is in Mohammad Hatta Islamic Elementary School, Malang City. The data collection techniques used observation, interview, and observation techniques. This study uses a key informant, the principal of SD Islam Mohammad Hatta. The results of the study show that the educational services marketing strategy in building the image of the school in the eyes of the community is successful, as seen from a positive assessment of the image of the school and the increase in the number of students from year to year. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan; (1) gambaran citra SD Islam Mohammad Hatta; (2) strategi pemasaran jasa pendidikan untuk citra kepada masyarakat di SD Islam Mohammad Hatta; (3) keberhasilan hasil strategi pemasaran untuk citra kepada masyarakat. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus deskriptif. Lokasi penelitian ini berada di SD Islam Mohammad Hatta kota Malang. Teknik pengumpulan data menggunakan teknik observasi, wawancara, dan observasi. Penelitian ini menggunakan informan kunci Kepala sekolah SD Islam Mohammad Hatta. Hasil dari penelitian menunjukkan strategi pemasaran jasa pendidikan dalam membangun citra sekolah dimata masyarakat berhasil, dilihat dari penilaian yang positif mengenai citra sekolah dan peningkatan jumlah peserta didik dari tahun ke tahun.